An Expert System To Diagnose Bronchitis Disease Using Certainty Factor Method - Septiyadi, Muhammad Harri; Yupianti, Yupianti; Zulfiandry, Ricky (LPPJPHKI Universitas Dehasen Bengkulu, 2023)
This study aims to create an expert system at Rafflesia Hospital of Bengkulu City, based on a website and using the PHP programming language, in diagnosing bronchitis using the certainty factor method, therefore the results of the diagnosis can be first aid when a user or patient suffers from bronchitis. The research method used is the certainty factor method, namely the certainty factor, thus the user or patient can choose. conditions according to the symptoms experienced from bronchitis. The program created is an expert system for diagnosing bronchitis using a website-based certainty factor method so that it can be accessed on laptops, computers, or mobile phones with the condition that it must be connected to the internet. This program can generate a percentage level of the possibility of how many percent of patients suffer from bronchitis, and this program also produces solutions to bronchitis therefore, it can be first aid when the user or patient suffers from bronchitis. Suggestions from the author are for agencies to be able to maintain and always update this expert system program, so then this system can run and be maintained properly.